Sistema de comunicação para rede de sensores sem fio aplicada ao controle ambiental - Fidanza, Letícia Barbosa [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The Internet of Things (IoT)concept proposes connectivity as an agent of daily routines, making it easier to manage tasks. In the agricultural production environment, for example, the use of IoT promotes numerous benefits in control and maintenance. With the increase of the world population it becomes necessary the use of mechanisms, in order to optimize the productivity and predictability in the productive process. In this context,Wireless Sensor Networks (WSNs) are tools used for environmental control in the field. The automation of agricultural production and monitoring are necessary for rapid decision-making, increasing agricultural production beyond saving natural resources, avoiding waste with irrigation and loss of production due to climatic conditions. The greatest difficulties encountered are the lack of knowledge about the application of technologies in the agricultural sector, the infrastructure and the interoperability with other control systems for rural automation. In this way, this project intends to implement a scalable and applicable solution for both the small and the large producer. Through the survey of the main relevant aspects in the implementation of the technology in the field and the construction of an WSN capable of acquiring data such as temperature and humidity, to process and transmit to the user in an interface that facilitates the decision making and control on its planting, down cost and in a sustainable way, taking into account the conditions of the studied environment, the technical and environmental impact of the implementation of this solution

O conceito de Internet das Coisas ( Internet of Things-IoT) propõe a conectividade como agente das rotinas diárias, facilitando no gerenciamento das tarefas. No ambiente de produção agrícola, por exemplo, o uso da IoT promove inúmeros benefícios no controle e na manutenção das tarefas no campo. Com o aumento da população mundial torna-se necessário o uso de mecanismos, afim de otimizar a produtividade e previsibilidade no processo produtivo. Nesse contexto, as Redes de Sensores Sem Fio (RSSF) são ferramentas utilizadas para controle ambiental na lavoura. A automação da produção agrícola e o monitoramento são necessários para rápidas tomadas de decisão, aumento da produção agrícola, além da economia de recursos naturais, evitando-se desperdícios com a irrigação e a perda de produção pelas condições climáticas. As maiores dificuldades encontradas são o desconhecimento quanto à aplicação das tecnologias no setor agropecuário, à infraestrutura e à interoperabilidade com outros sistemas de controle para automação do meio rural. Dessa maneira, este projeto tem o intuito de implementar uma solução escalável e aplicável, tanto para o pequeno, quanto para o grande produtor. Por meio do levantamento dos principais aspectos relevantes na implementação da tecnologia no campo e da construção de uma RSSF capaz de adquirir dados como temperatura e umidade, processar e transmitir ao usuário em uma interface que facilite as tomadas de decisões e controle sobre sua plantação, a baixo custo e de forma sustentável, levando em conta as condições do ambiente estudado e o impacto técnico e ambiental da implementação dessa solução
Communication system for wireless sensor network applied to environmental control
Keywords: Detectores; Fazendas; Internet; Monitoramento ambiental; Redes de sensores sem fio; Sustentabilidade; Telecomunicações; Detectors; Environmental monitoring; Farms; Sustainability; Telecommunication; Wireless sensor networks